2021
DOI: 10.3390/app11031195
|View full text |Cite
|
Sign up to set email alerts
|

Hair-Growth-Promoting Effects of Fermented Red Ginseng Marc and Traditional Polyherb Formula in C57BL/6 Mice

Abstract: An abnormal hair-growth cycle induces hair loss, which affects psychological distress and impairs life quality. Red ginseng marc (RGM) is usually discarded as a byproduct after extracting red ginseng, but several studies have shown that the RGM still has bioactive components including ginsenosides. Therefore, the hair-growth effects of fermented RGM (fRGM) and traditional polyherb formula (PH) were examined in C57BL/6 mice. The dorsal hairs of mice were depilated, and they were topically treated with fRGM or P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Generally, growth factors such as IGF-1, VEGF, fibroblast growth factor, and keratinocyte growth factors stimulate the proliferation of hair cells, maintain the development of hair follicles, and enhance hair growth and hair shaft elongation. In contrast, other growth factors, such as TGF-β, fibroblast growth factor 5, and prostaglandin D2, can inhibit hair growth ( Herman and Herman, 2016 ; Park and Lee, 2021 ; Song et al, 2021 ). The results of the current study indicated that topical application of RHSO enhanced the level of IGF-1 in mouse skins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, growth factors such as IGF-1, VEGF, fibroblast growth factor, and keratinocyte growth factors stimulate the proliferation of hair cells, maintain the development of hair follicles, and enhance hair growth and hair shaft elongation. In contrast, other growth factors, such as TGF-β, fibroblast growth factor 5, and prostaglandin D2, can inhibit hair growth ( Herman and Herman, 2016 ; Park and Lee, 2021 ; Song et al, 2021 ). The results of the current study indicated that topical application of RHSO enhanced the level of IGF-1 in mouse skins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Promoting effects on the hair growth cycle [163] Carrot root Bacillus ginsengisoli Anti-oxidant, reduced skin dullness, anti-aging, anti-wrinkle [132] Radish root…”
Section: Bioferments In the Cosmetic Industrymentioning
confidence: 99%
“…Fermented RGM was provided by Punggi Ginseng Farming Corp. (Yeongju, Korea), and used as same lot number as that used in our previous study [25]. Briefly, 6-year-old Korean red ginseng was extracted by boiling in distilled water (DW) for 3 h at 80 °C, and the remaining RGM was dried and grinded.…”
Section: Preparation Of Fermented Rgmmentioning
confidence: 99%
“…Fermented RGM contains a greater proportion of ginsenosides, Rg2, Rg3 and Rh2 than the non-fermented RGM, which enhances its antioxidant activities and incidental favorable effects [23,24]. Our previous study has shown that topical treatment of RGM extracts fermented with a complex of microorganisms promotes hair growth [25]. The fermented RGM contained crude ginsenosides (1.7 mg/g) and polyphenols (9.8 mg/g), and the antioxidant activities were more than those of non-fermented form.…”
Section: Introductionmentioning
confidence: 99%